The expression that is correctly developed to use the power rule of exponents is:
(7^(8)) . (7^(10)) = 7^(8+10) = 7^(18)
Which expression is correctly developed to use the power rule of exponents(
(7^(8)) . (7^(10))
(-5)^(8)
(7^(4))^(8)
12^(9)
9 answers
which of the following correctly used the power rule of exponents in the expressions (10^(9))(7)
90^(7)
10^(63)
10^(16)
10^(2)
90^(7)
10^(63)
10^(16)
10^(2)
The expression that correctly uses the power rule of exponents is:
(10^(9))(7) = 10^(9+1) = 10^(10)
(10^(9))(7) = 10^(9+1) = 10^(10)
if the expression 4^(10) was simplified using the power rule of exponents what is an equivalent expanded expression
The equivalent expanded expression, when simplifying 4^(10) using the power rule of exponents, would be:
4^(10) = 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4
4^(10) = 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4 * 4
Use the power rule of exponents to create an expression equivalent to ((15^(6))(2)
Using the power rule of exponents, the equivalent expression to ((15^(6))(2)) can be written as:
(15^(6))(2) = 15^(6+1) = 15^(7)
(15^(6))(2) = 15^(6+1) = 15^(7)
what exponent would make the two expressions equivalent ((3^(9))(x) = (3^(24)
To make the two expressions ((3^(9))(x) and (3^(24)) equivalent, the value of x would need to be:
x = 3^(24-9) = 3^15
x = 3^(24-9) = 3^15